Leadership in Action - Issues and Observations - Finding Success at Succession - Berke, David (Center for Creative Leadership, 2002)
In recent years, succession planning-which aims to ensure continuity in key leadership and management functions-has become increasingly important for organizations.
Title from content provider
Keywords: Leadership